Strategic Role of Libero in Improving Team Performance in Volleyball: A Literature Review - Ahmad Robi Alfaini; Soni Sulistyarto; Achmad Widodo; Muhammad Arja Bahauddin (Universitas Negeri Surabaya, 2026)
Background: The purpose of this study was to determine how a libero contributes to a team during a volleyball match. The method used was a literature review. Literature searches were conducted through the Google Scholar database, focusing on articles published between 2020 and 2025. The keywords used were contribution, libero, and volleyball. Methods: The article screening process for this literature review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A total of 333 articles were initially identified and then filtered according to the inclusion criteria: (1) international articles published in English, and (2) articles accessible online and available for download. After screening, 94 articles related to the libero's contribution to volleyball matches were selected for further review. Ultimately, 8 articles met all eligibility criteria and were included in the study. Results: The findings of this literature review indicate that liberos possess valuable and highly effective skills that contribute significantly to team performance. These skills include high-quality serve reception, setting as a secondary setter, and strong defensive abilities. These elements are essential in volleyball because they help maintain the balance between offense and defense and enhance the competitiveness of the game. Conclusion: The libero plays a crucial role in volleyball by providing effective serve reception, acting as a secondary setter when necessary, and contributing strong defensive performance. These skills support the balance between attack and defense, thereby improving overall team performance and making matches more competitive.